2011
DOI: 10.1007/s10615-011-0334-5
|View full text |Cite
|
Sign up to set email alerts
|

The Tango of Loving Hate: Couple Dynamics in High-Conflict Divorce

Abstract: This article explores the dynamics of couples embroiled in high-conflict divorce through the theoretical prism of British object relations theory. Such couples are often characterized by primitive object relations, and use splitting and projection as a way of ''being in the world.'' The fear of the ex-spouse's retaliation is accompanied by fear of their own destructiveness and a desire to make reparation; however, attempts at reparation at this level of relational functioning rarely achieve reconciliation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 20 publications
2
31
0
3
Order By: Relevance
“…An Israeli team consisting of an experienced family therapist and academic scholar subsequently undertook research that confirmed many of our observations (Levite, ; Levite & Cohen, ; Cohen & Levite, ). They reanalyzed research records from the Judith Wallerstein Family in Transition data bank, comparing groups of families from the normal community with high‐conflict, litigating, and violent court‐referred cases and interpreted the findings through the theoretical lens of British Object Relations theory.…”
supporting
confidence: 68%
“…An Israeli team consisting of an experienced family therapist and academic scholar subsequently undertook research that confirmed many of our observations (Levite, ; Levite & Cohen, ; Cohen & Levite, ). They reanalyzed research records from the Judith Wallerstein Family in Transition data bank, comparing groups of families from the normal community with high‐conflict, litigating, and violent court‐referred cases and interpreted the findings through the theoretical lens of British Object Relations theory.…”
supporting
confidence: 68%
“…Instead, their lives seem to be ruled by an obsessive focus on the object(s) of their hatred. Unfettered, hatred can become all consuming, leaving little room for self‐awareness or reflective capacity (Levite, ; Lichtenberg & Shapard, ; Wolf, ). It can become both a passion and a raison d'etre —one in which some individuals even find joy in initiating actions that cause the hated object pain and humiliation (Gaylin, ; Yanay, ).…”
Section: Hatred and Its Key Ingredientsmentioning
confidence: 99%
“…Partners lack ways to cope with frustration, anger, rage, hate, pain or ambivalence. They cannot bear the anxiety these produce and try to resolve it in a way that exacerbates conflict in the marriage or in a divorce (Klein 1940; Levite, 2003; Ogden, 1990).…”
Section: The Divorce Process and High Conflict Couplesmentioning
confidence: 99%
“…The process of retaliation is a process that is activated by destructiveness, rage and hate. The parallel process of reparation is activated by the need to feel that love is stronger than hate (Klein, 1940; Levite, 2003; Ogden, 1990; Winnicott, 1968). Retaliation is a mechanism used by individuals who fear their own feelings of rage and aggression, as well as their own destructiveness.…”
Section: The Divorce Process and High Conflict Couplesmentioning
confidence: 99%
See 1 more Smart Citation